2016
DOI: 10.1007/s00018-016-2351-6
|View full text |Cite
|
Sign up to set email alerts
|

Back to the tubule: microtubule dynamics in Parkinson’s disease

Abstract: Cytoskeletal homeostasis is essential for the development, survival and maintenance of an efficient nervous system. Microtubules are highly dynamic polymers important for neuronal growth, morphology, migration and polarity. In cooperation with several classes of binding proteins, microtubules regulate long-distance intracellular cargo trafficking along axons and dendrites. The importance of a delicate interplay between cytoskeletal components is reflected in several human neurodegenerative disorders linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 286 publications
(395 reference statements)
2
105
0
Order By: Relevance
“…The staining of pSer129 + inclusions with the Proteostat aggresomal dye is consistent with previous studies on similarities between Lewy bodies and aggresomes (112,161). The formation of the aggresome is microtubule-dependent (96) and α-synuclein appears to interact with tubulin, perhaps serving as a microtubule dynamase (6,37,135). Aggresomes are hypothesized to serve as a protective mechanism facilitating cellular survival under proteotoxic conditions (162), as they are observed in 53%-60% of nonapoptotic cells but only 10%-13% of apoptotic cells in vitro (161).…”
Section: α-Synucleinopathic Inclusions In the Preformed Fibril Model supporting
confidence: 89%
“…The staining of pSer129 + inclusions with the Proteostat aggresomal dye is consistent with previous studies on similarities between Lewy bodies and aggresomes (112,161). The formation of the aggresome is microtubule-dependent (96) and α-synuclein appears to interact with tubulin, perhaps serving as a microtubule dynamase (6,37,135). Aggresomes are hypothesized to serve as a protective mechanism facilitating cellular survival under proteotoxic conditions (162), as they are observed in 53%-60% of nonapoptotic cells but only 10%-13% of apoptotic cells in vitro (161).…”
Section: α-Synucleinopathic Inclusions In the Preformed Fibril Model supporting
confidence: 89%
“…Destabilization of the MT network and defective interplay among cytoskeletal components has been observed in PD and other neurological disorders, as well as in cancer and inflammation . Drug‐like agents that modulate MT stability or inhibit post‐translational modifiers affecting the levels of tubulin acetylation constitute the most addressed therapeutic interventions aiming to prevent cytoskeletal damage in neurodegenerative disorders . MT stabilizers such as epithilone D displayed beneficial effects in some PD model .…”
Section: Tppp/p25: the New Hallmark Of Parkinsonismmentioning
confidence: 99%
“…Low tubulin acetylation levels, along with a concomitant impairment in axonal transport, is a common pathological hallmark in several neurodegenerative diseases; the application of drugs targeting MT acetylation is considered to be a useful strategy for therapeutic intervention . Indeed, specific HDAC6 inhibitors exerted neuroprotection, rescued transport defects in some PD models . Sirtuin‐2 inhibitors also rescued SYN toxicity in different cellular and animal models of PD .…”
Section: Tppp/p25: the New Hallmark Of Parkinsonismmentioning
confidence: 99%
“…These data suggest a functional link between MT acetylation patterns and brain aging, evidencing how the regulation of MT stability is critical during normal neuronal aging and supporting the concept that its failure may be a reliable candidate in causing neurodegenerative processes. Indeed, during the last years, an increasing body of evidence indicated the potential role of defective regulation of MT stability in neurodegenerative disorders [18] and, in particular, in Parkinson's Disease (PD) [19,20].PD is the second most common neurodegenerative disorder caused by the death of the dopaminergic neurons in the Substantia nigra [21] whose anatomy, with an average arborisation of 4.6 meters in humans [22], makes them particularly dependant on axonal transport which, in turn, depends on MT integrity and whose failure has been associated to the early phases of PD [23]. Although the identity of the real culprit of the pathology is still debated, in the recent years it is becoming ever clearer that MT destabilization is an early event in experimental and human models of PD, and many of the studies reported below strongly suggest that it can be followed by the hyper-stabilization of MTs, which could lead to detrimental side effects.…”
mentioning
confidence: 99%
“…These data suggest a functional link between MT acetylation patterns and brain aging, evidencing how the regulation of MT stability is critical during normal neuronal aging and supporting the concept that its failure may be a reliable candidate in causing neurodegenerative processes. Indeed, during the last years, an increasing body of evidence indicated the potential role of defective regulation of MT stability in neurodegenerative disorders [18] and, in particular, in Parkinson's Disease (PD) [19,20].…”
mentioning
confidence: 99%